Reasoning about counterfactual conditionals : the role of content, tense and linguistic form - Egan, Suzanne (Trinity College (Dublin, Ireland). School of Psychology, 2005)
The primary aim of this thesis is to investigate reasoning from counterfactual conditionals (e.g., if Rosanna had been in Dublin then Anthony would have been in Roscommon) and to test predictions derived from the mental model theory account of reasoning from counterfactual conditionals (Johnson-Laird & Byrne, 1991; 2002). The mental model theory of reasoning proposes that people reason conditionally by keeping possibilities in mind. We aim to extend the theory to account for the role of content, tense and linguistic form in reasoning from counterfactual conditionals.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin